2022
DOI: 10.3389/fnagi.2021.734382
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Strain Among Caregivers of Persons Living With Dementia

Abstract: ObjectiveThe study objective was to examine predictors of sleep disturbance and strain among caregivers of persons living with dementia (PLWD).MethodsThis cross-sectional study utilized a sample of community-dwelling older adults and their family caregivers drawn from the 2017 National Health and Aging Trends Study and National Study of Caregiving. Multivariable logistic regression was used to assess the association between caregiver and PLWD characteristics and a composite measure of caregiving strain. High c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Eighteen studies investigated the association between caregiver burden and self-reported sleep quality. Fourteen of these studies found a significant correlation between greater caregiving burden and worse sleep quality ( 26 , 31–43 ), whereas the remaining 4 studies showed that caregiver burden was not significantly correlated with subjective sleep quality measures ( 28 , 29 , 44 , 45 ). Of the 14 studies that measured overall sleep quality using the PSQI, 12 studies found a significant correlation between caregiving burden and overall sleep quality, while 2 did not ( 28 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies investigated the association between caregiver burden and self-reported sleep quality. Fourteen of these studies found a significant correlation between greater caregiving burden and worse sleep quality ( 26 , 31–43 ), whereas the remaining 4 studies showed that caregiver burden was not significantly correlated with subjective sleep quality measures ( 28 , 29 , 44 , 45 ). Of the 14 studies that measured overall sleep quality using the PSQI, 12 studies found a significant correlation between caregiving burden and overall sleep quality, while 2 did not ( 28 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Caregivers usually spend 14.3 hours per day in care tasks 13 , 18 , 19 , 22 , 33 , being responsible for the PLwD for nearly 5.7 years 1 , 14 , 17 , 22 , 25 , 31 , 32 , 33 . The mean age of caregivers in the selected studies was 60.3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Caregivers of PLwD tend to spend less than 7 hours in bed, having high amounts of wake, impacting not only sleep quantity but also sleep quality 6 . Studies have found negative impacts in sleep latency 1 , 7 , 18 , 27 , 32 , sleep fragmentation 13 , 18 , 19 , 26 , shorter sleep duration 3 , 18 , and low subjective sleep quality 1 , 2 , 33 . In smaller proportions, they found insomnia 8 , use of medication 1 , 29 , daytime dysfunction 3 , and low sleep efficiency 1 , 6 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 As a result, long-term stress and reduced sleep quality lead to caregivers having an increased risk of health problems, such as heart disease and cognitive decline. 5,9 Caregiver stress also contributes to worsening neuropsychiatric symptoms in people with dementia from the negative emotions of caregivers that can result in frustration, irritation, and anger. 10 Thus, helping caregivers to manage their stress benefits not only their own health and sleep but also improves their interactions with family members with dementia.…”
mentioning
confidence: 99%